Local Wisdom-Based Rice Field Conservation Through Meugoe Customary Practices in Aceh Besar, Indonesia - Evi Apriana; Erdi Surya; Nurul Akmal; Elvrida Rosa; Elfa Yeni (Jurnal Penelitian Pendidikan IPA, 2026)
This research aims to analyze the local wisdom of the community in rice field conservation and identify customary sanctions for violations that occur. The research uses a qualitative approach with data collection techniques in the form of observation and interviews. The research subjects consisted of the imeum mukim, keujreun blang, and the community of Ateuk Mon Panah Village, Simpang Tiga District, Aceh Besar Regency, with a total of 30 respondents. The results of the study show that local wisdom in the form of meugoe (rice fields) customs, especially related to the order of going down to the rice fields, has been inherited from generation to generation and is still maintained to this day. In addition, there are customary sanctions imposed for violations, such as water theft, in the form of sanctions in the form of the obligation to make talam cakes up to 1000 pieces or the slaughter of goats, depending on the level of violation. Local wisdom in the practice of meugoe has been proven to be in line with the principles of rice field and environmental conservation. Therefore, the preservation of these traditional values is important to support environmental sustainability and can be used as a source of learning for the community and the world of education.